2021
DOI: 10.3390/ijms22042215
|View full text |Cite
|
Sign up to set email alerts
|

GBA Mutations Influence the Release and Pathological Effects of Small Extracellular Vesicles from Fibroblasts of Patients with Parkinson’s Disease

Abstract: Heterozygous mutations in the GBA gene, encoding the lysosomal enzyme glucocerebrosidase (GCase), are the strongest known genetic risk factor for Parkinson’s disease (PD). The molecular mechanisms underlying the increased PD risk and the variable phenotypes observed in carriers of different GBA mutations are not yet fully elucidated. Extracellular vesicles (EVs) have gained increasing importance in neurodegenerative diseases since they can vehiculate pathological molecules potentially promoting disease propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…In homozygous and heterozygous form, E326K mutations are not associated with a significant loss of GCase expression or activity in fibroblasts and SH-SY5Y cells. These findings are supported by previous literature demonstrating the E326K variant generally reduces GCase activity to a lesser extent than other pathogenic GBA mutations (16,(56)(57)(58)(59)(60)(61), while L444P and N370S variants are reported to induce a loss of GCase function (30,31,42,(61)(62)(63)(64)(65)(66)(67), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In homozygous and heterozygous form, E326K mutations are not associated with a significant loss of GCase expression or activity in fibroblasts and SH-SY5Y cells. These findings are supported by previous literature demonstrating the E326K variant generally reduces GCase activity to a lesser extent than other pathogenic GBA mutations (16,(56)(57)(58)(59)(60)(61), while L444P and N370S variants are reported to induce a loss of GCase function (30,31,42,(61)(62)(63)(64)(65)(66)(67), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The plasma exosomal/total α-syn ratio is associated with GCase activity, and it correlates with severity (motor deficiency) in PD patients ( Cerri et al, 2018 ; Johnson et al, 2020 ), proposing the link between lysosomal dysfunction with increased exosome secretion. Similar results were reported in fibroblasts derived from PD patients with or without GBA1 , in which defective GCase activity increased the release of exosomes ( Cerri et al, 2021 ). Isolated exosomes from these cells caused increased levels of phospho-α-syn in SH-SY5Y recipient cells, overexpressing wild-type α-syn ( Cerri et al, 2021 ).…”
Section: Impact Of Autophagy-lysosomal Pathway In Parkinson’s Disease...supporting
confidence: 84%
“…Similar results were reported in fibroblasts derived from PD patients with or without GBA1 , in which defective GCase activity increased the release of exosomes ( Cerri et al, 2021 ). Isolated exosomes from these cells caused increased levels of phospho-α-syn in SH-SY5Y recipient cells, overexpressing wild-type α-syn ( Cerri et al, 2021 ). Interesting, this effect was not due to a seeding effect since fibroblasts are α-syn-free.…”
Section: Impact Of Autophagy-lysosomal Pathway In Parkinson’s Disease...supporting
confidence: 84%
“…The expression of α-Syn in the skin has been mainly ascribed to peripheral nerve terminals and melanocytes (Rodriguez-Leyva et al, 2016; Kim et al, 2019). Dermal fibroblasts are also another possible source of α-Syn accumulation in the aged skin, releasing exosomes containing α-Syn and pro-inflammatory mediators by cell-to-cell transmission from the dermis to the epidermis (Danzer et al, 2012; Cerri et al, 2021). However, one study also showed α-Syn immunopositive keratinocytes from the skin of patients with Parkinson’s disease and atypical parkinsonism (Rodríguez-Leyva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%